Protease-sensitive pancreatic lipase variants are associated with early onset chronic pancreatitis - Lasher, Denise; Szabó, András; Masamune, Atsushi; Chen, Jian-Min; Xiao, Xunjun; Whitcomb, David C.; Barmada, M. Michael; Ewers, Maren; Ruffert, Claudia; Paliwal, Sumit; Issarapu, Prachand; Bhaskar, Seema; et al. (The American journal of gastroenterology, 2019)
OBJECTIVES: Premature activation of the digestive protease trypsin within the pancreatic parenchyma is a critical factor in the pathogenesis of pancreatitis. Alterations in genes that affect intrapancreatic trypsin activity are associated with chronic pancreatitis (CP). Recently, carboxyl ester lipase emerged as a trypsin-independent risk gene. Here, we evaluated pancreatic lipase (PNLIP) as a potential novel susceptibility gene for CP. - METHODS: We analyzed all 13 PNLIP exons in 429 nonalcoholic patients with CP and 600 control subjects from Germany, in 632 patients and 957 controls from France, and in 223 patients and 1,070 controls from Japan by DNA sequencing. Additionally, we analyzed selected exons in further 545 patients with CP and 1,849 controls originating from Germany, United States, and India. We assessed the cellular secretion, lipase activity, and proteolytic stability of recombinant PNLIP variants. - RESULTS: In the German discovery cohort, 8/429 (1.9%) patients and 2/600 (0.3%) controls carried a PNLIP missense variant (P = 0.02, odds ratio [OR] = 5.7, 95% confidence interval [CI] = 1.1-38.9). Variants detected in patients were prone to proteolytic degradation by trypsin and chymotrypsin. In the French replication cohort, protease-sensitive variants were also enriched in patients with early-onset CP (5/632 [0.8%]) vs controls (1/957 [0.1%]) (P = 0.04, OR = 7.6, 95% CI = 0.9-172.9). In contrast, we detected no protease-sensitive variants in the non-European populations. In the combined European data, protease-sensitive variants were found in 13/1,163 cases (1.1%) and in 3/3,000 controls (0.1%) (OR = 11.3, 95% CI = 3.0-49.9, P < 0.0001). - CONCLUSIONS: Our data indicate that protease-sensitive PNLIP variants are novel genetic risk factors for the development of CP.
Gesehen am 31.10.2019